Towards a Monte Carlo simulation of a pebble bed type high temperature gas cooled reactor using Geant4. (April 2022) - Cilliers, A.C.; Connell, S.H.; Conradie, J.; Cook, M.N.H.; Laassiri, M.; Maqabuka, B.G.; Mudau, R.; Naidoo, P.; Nicholls, D.
Highlights: Monte Carlo Simulation. Stochastic Reactor Neutronics. Geant4 for Neutronics. Abstract: This paper introduces the stochastic Monte Carlo (MC) modelling of a nuclear reactor core using the Geant4 framework. The simulation is exercised in the context of a High Temperature Gas Cooled Reactor (HTGCR) that uses helium (a noble gas) as a coolant and graphite as a neutron moderator. The study presents the results from the implementation of basic neutronics, scalability, geometrical discretisation for studying the spatial variation of physical parameters, time slicing and adaptation of Geant4 for correct intra-slice persistence, a scheme of integration with thermal hydraulics by workflow scheduling, validation of the thermal macroscopic cross-section behaviour, the process of fission, burn, decay, and differential energy depositions for the various physics processes, validation of the Xenon effects on the neutronics, criticality and core follow over multiple time steps.